Peran Baitul Mal Langsa dalam Pengelolaan Zakat dan Infaq untuk Meningkatkan Pemberdayaan Masyarakat - Jauwahir Jauwahir; Heri Kusmanto; Isnaini Isnaini (Universitas Medan Area, 2021)
This study aims to find out what the role of Baitul Mal in Langsa City is in Managing Zakat and Infaq to empower underprivileged communities identified as mustahik in Langsa City. various ways and means. The meaning of infaq is also something that is spent for good. Infaq also does not have a time limit as well as large and small. This type of research is Field Research or field research that is case study, namely research that is carried out intensively in detail and in depth on an organization, institution or particular phenomenon by collecting the necessary information by visiting homes or places of people or agencies who information will be asked. The approach used in this research is qualitative, namely research that needs to be carried out after the problem is researched qualitatively, but the solution has not been revealed. This research consists of primary data and secondary data. Primary data is obtained from survey results or results of in-depth interviews with the Head of Baitul Mal, Secretary and Staff or management who are the key to the ongoing activities of Zakat and Infaq Distribution. Meanwhile, secondary datasets were obtained by researchers from existing sources, such as an overview of the company, organizational structure, and so on. The results of the study show that Baitul Mal has a role to take care of, manage, collect, distribute, and utilize zakat. The collection of zakat is carried out by receiving or taking from the person who issued the zakat (muzakki) based on the notification of the muzakki.